The Antibacterial and Antibiofilm Activity of Telithromycin Against Enterococcus spp. Isolated From Patients in China - Xiong, Yanpeng; Chen, Junwen; Sun, Xiang; Xu, Guangjian; Li, Peiyu; Deng, Qiwen; Yu, Zhijian; Chen, Zhong; Zheng, Jinxin (Frontiers in Microbiology, 2021)
Telithromycin has been reported to possess robust in vitro antibacterial activity against many species of Gram-positive bacteria, and telithromycin is also effective against Staphylococcus aureus biofilms. However, the in vitro antimicrobial susceptibility of telithromycin against clinical enterococci isolates in China is rarely reported and the impacts of telithromycin on the biofilm formation and eradication of enterococci remain elusive. Therefore, this study aimed to explore the inhibitory effects of telithromycin on planktonic cells and biofilms of Enterococcus strains. A total of 280 Enterococcus faecalis and 122 Enterococcus faecium isolates were collected from individual inpatients in China. The 50% minimum inhibitory concentration (MIC50) values of telithromycin against E. faecalis and E. faecium strains carrying erythromycin-resistant methylase (erm) genes such as the ermA, ermB, or ermC, were 2 g/mL and 4 g/mL respectively. In addition, these isolates were typed using multilocus sequence typing (MLST) based on housekeeping genes. The predominant sequence types (STs) of E. faecalis were ST16, ST30 and ST179, and the main STs of E. faecium isolates were ST18, ST78, and ST80. Among these major STs, 87.1% (135/158) of E. faecalis and 80.4% (41/51) of E. faecium carried erm genes. Furthermore, at the subinhibitory concentrations (1/4 and 1/8×MIC) of telithromycin, the biofilms formation of 16 E. faecalis isolates were inhibited by approximately 35%. Moreover, treatment with 8×MIC of telithromycin or ampicillin led to almost 40% reduction in the established biofilms of E. faecalis isolates, whereas vancomycin or linezolid with 8×MIC had minimal effects. The combination of telithromycin and ampicillin resulted in almost 70% reduction in the established biofilms of E. faecalis. In conclusion, these results revealed that telithromycin significantly decreased planktonic cells of both E. faecalis and E. faecium. In addition, the data further demonstrated that telithromycin was effective against E. faecalis biofilms. These in vitro antibacterial and antibiofilm activities suggest that telithromycin could be a potential candidate for treatment of enterococcal infections.